Distribution of travel distances from field-measured tracer data, two-dimensional modeling data and probabilistic modeling data in the Ain River (2013-2017) - Arnaud, Fanny; Paquier, André; Vázquez-Tarrío, Daniel; Camenen, Benoit; Le Coz, Jérôme; Michel, Kristell; Naudet, Grégoire; Pella, Hervé; Piégay, Hervé (In: Arnaud, F et al. (2023): Field, probabilistic and 2D numerical modeling dataset on gravel mobility in the Ain River (2013-2017) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.954231, 2023)
This dataset describes the distribution (in number of tracers) of downstream travel distances calculated from field-measured PIT-tagged particles, two-dimensional hydrodynamic modeling and probabilistic modeling in the Ain River channel over the periods 2013-2014, 2013-2015 and 2013-2017.
Keywords: 2D modeling; Ain River; Gravel mobility; PIT tags; Probabilistic modeling